Poverty, Unemployment, and Banditry in Nigeria: A Political Economy View - Adedeji Daniel Gbadebo (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study investigates the relationship between poverty, unemployment, and banditry in Nigeria from a political economy perspective. Using survey data from 300 respondents in Bida Local Government Area, Niger State, chi-square tests revealed significant associations between poverty and banditry (χ² = 23.476, p = 0.002), unemployment and banditry (χ² = 18.129, p = 0.001), and political economy factors and banditry (χ² = 21.334, p < 0.001). The findings show that 91% of respondents perceive poverty as widespread, 84% link high poverty rates to criminal activity, and 87% believe youth unemployment contributes to banditry. Weak governance, corruption, and poor resource allocation were also identified by over 86% of participants as key enablers of insecurity. Applying Queer Ladder Theory, the study concludes that structural inequalities and limited legitimate economic opportunities push marginalized groups toward criminal enterprises. It recommends targeted poverty reduction, youth job creation, anti-corruption reforms, and enhanced government presence in rural areas to address the root causes of banditry.